METABOLIC SYSTEM OF CHOLESTEROL ELIMINATION FROM TISSUES. POSSIBILITY OF ACTIVATION ITS KEY PARTS - N. V. Perova; I. N. Ozerova; V. A. Metelskaya (Рациональная фармакотерапия в кардиологии)
Lipid metabolism issues are reviewed. Ways of cholesterol transformation are represented thoroughly; proteins regulating its transportation are described. Important place takes the role of high density lipoproteins in backward transportation of cholesterol from peripheral tissues. Possibilities of pharmacological activation of this system, aimed at prevention and treatment of atherosclerosis are discussed.